A pilot double‐blind safety and feasibility randomized controlled trial of high‐dose intravenous zinc in hospitalized COVID‐19 patients. Issue 5 (9th March 2021) - Patel, Oneel; Chinni, Vidyasagar; El‐Khoury, John; Perera, Marlon; Neto, Ary S.; McDonald, Christine; See, Emily; Jones, Daryl; Bolton, Damien; Bellomo, Rinaldo; Trubiano, Jason; Ischia, Joseph
Abstract: Zinc inhibits replication of the SARS‐CoV virus. We aimed to evaluate the safety, feasibility, and biological effect of administering high‐dose intravenous zinc (HDIVZn) to patients with COVID‐19. We performed a Phase IIa double‐blind, randomized controlled trial to compare HDIVZn to placebo in hospitalized patients with COVID‐19. We administered trial treatment per day for a maximum of 7 days until either death or hospital discharge. We measured zinc concentration at baseline and during treatment and observed patients for any significant side effects. For eligible patients, we randomized and administered treatment to 33 adult participants to either HDIVZn ( n = 15) or placebo ( n = 18). We observed no serious adverse events throughout the study for a total of 94 HDIVZn administrations. However, three participants in the HDIVZn group reported infusion site irritation. Mean serum zinc on Day 1 in the placebo, and the HDIVZn group was 6.9 ± 1.1 and 7.7 ± 1.6 µmol/l, respectively, consistent with zinc deficiency. HDIVZn, but not placebo, increased serum zinc levels above the deficiency cutoff of 10.7 µmol/l ( p < .001) on Day 6. Our study did not reach its target enrollment because stringent public health measures markedly reduced patient hospitalizations. Hospitalized COVID‐19 patients demonstrated zinc deficiency. This can be corrected with HDIVZn. Such treatment appears safe, feasible, and only associated with minimal peripheral infusion site irritation. This pilot study justifies further investigation of this treatment in COVID‐19 patients.